Criminology of Corruption in Indonesia: Analysis of Perpetrator Behavior Patterns and Social Determinants - Josmangasi Simbolon; Parningotan Malau; Alwan Hadiyanto (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2026)
This article examines the criminological dimensions of corruption in Indonesia through an analysis of perpetrator behavior patterns and the social factors that influence them. Using a qualitative-empirical approach, this study combines public data from legal institutions such as the Corruption Eradication Commission (KPK), the Supreme Court (MA), the Attorney General's Office, the Police, and the Supreme Audit Agency (BPK) with the results of simulated interviews designed to understand the moral rationalization of perpetrators of corruption. The results show that corruption is not merely a violation of the law, but rather a systemic social behavior that is learned within bureaucratic structures and permissive organizational cultures. This study also finds disparities in sentencing between perpetrators of corruption and perpetrators of general crimes, indicating the persistence of class bias and the weak deterrent effect of Indonesia's legal system. This article concludes that corruption eradication reforms must be directed at structural and moral reconstruction, by enforcing proportionality in punishment, strengthening institutional control, and fostering a culture of integrity and justice.